2018
DOI: 10.1016/j.celrep.2018.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Sub-populations of Spinal V3 Interneurons Form Focal Modules of Layered Pre-motor Microcircuits

Abstract: SummaryLayering of neural circuits facilitates the separation of neurons with high spatial sensitivity from those that play integrative temporal roles. Although anatomical layers are readily identifiable in the brain, layering is not structurally obvious in the spinal cord. But computational studies of motor behaviors have led to the concept of layered processing in the spinal cord. It has been postulated that spinal V3 interneurons (INs) play multiple roles in locomotion, leading us to investigate whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 64 publications
(105 reference statements)
3
74
1
Order By: Relevance
“…V3 interneurons represent an additional class of commissural excitatory interneurons that are broadly distributed along the dorsal-ventral and rostral-caudal axes in the postnatal spinal cord (50,52,487). It has been shown that V3 interneurons, in addition to their commissural role, also provide ipsilateral excitation to each other and to motoneurons on the same side (96). Acute silencing of interneurons in the lumbar region of freely moving adult mice produced uneven gaits, suggesting that they play a role in limb coordination (487).…”
Section: ) (Figure 14c)mentioning
confidence: 99%
“…V3 interneurons represent an additional class of commissural excitatory interneurons that are broadly distributed along the dorsal-ventral and rostral-caudal axes in the postnatal spinal cord (50,52,487). It has been shown that V3 interneurons, in addition to their commissural role, also provide ipsilateral excitation to each other and to motoneurons on the same side (96). Acute silencing of interneurons in the lumbar region of freely moving adult mice produced uneven gaits, suggesting that they play a role in limb coordination (487).…”
Section: ) (Figure 14c)mentioning
confidence: 99%
“…A more recent set of experiments described excitatory motor neuron connectivity to one class of non-Renshaw interneuron. Chopek et al (2018) found that motor neurons in postnatal mice activate a population of ipsilateral V3 interneurons via glutamatergic synapses; V3 interneurons, in turn, project bilaterally to neurons in the locomotor CPG. When V3 interneuron signaling is suppressed, locomotor patterns become more variable and left-right alternation is disrupted, suggesting that V3 interneurons maintain robust, bilaterally symmetric locomotor rhythms (Zhang et al, 2008).…”
Section: Chordatamentioning
confidence: 99%
“…In the current study, novel optogenetic tools have enabled us to specifically Hägglund et al, 2013;Levine et al, 2014), reversibly, and acutely regulate the activity of a molecularly-identified group of spinal neurons. By using Sim1Cre/+; Ai32 mice (Chopek et al, 2018), we were able to target V3 interneurons on both or just one side of the isolated spinal cords allowing us to start dissecting the function of V3 CINs in spinal locomotor circuits.…”
Section: Optogenetic Activation Of V3 Interneuronsmentioning
confidence: 99%